Post-Secular Return of Religion: A Religion of Being-for-the-Other - Thomas, Rogi (IJRDO - Journal of Social Science and Humanities Research, 2017)
Secularism in conventional understanding involves a strict separation of the state from religious institutions. It ensures that religious groups do not impede affairs of the state. Equally it also makes sure that the state does not interfere in religious affairs. In this respect post-modernity offers a paradigm shift in the hermeneutical understanding of the conception of ‘secular’ and ‘religion’. This would entail Post-Secular Return of Religion: A Religion of Being-for-theOther which will be the crux of my argument. I draw cues from Charles Taylor, and Gianni Vattimo. (1) I claim that the basis of the post-secular return of religion is the ‘death of God’. (2) Thus, I argue for the hermeneutic recovery of the divine after the death of the metaphysical God. (3) It would be wrong to identify this hermeneutical recovery of God with a dimension of an individual belief system, something contained and conceded by it. Finally, (4) God is not seen as a being outside the universe, but within, being a potential promise present in language, culture, and in human lives, maturing the creature’s createdness. It enables ‘the self’ to realize its own being and of the other and thus to-be-for-the-other. Being-for-the-other is inevitable because the hermeneutic rediscovery of religion and sacred is (should be) primarily aimed at human flourishing and peaceful coexistence of the whole of creation, man and beast alike. This post-secular return of religion as ‘being-for-the-other’ visualises a pluralistic community which rejuvenates social discourse, practices of economic development, and new ecological policies within democratic countries. The paper will explain these implications in detail.